Analisis Informasi Keuangan Dalam Mengevaluasi Kinerja Pemerintah Kabupaten Batu Bara - Purba, Sahala; Pratama, Putra; Panjaitan, Lady Cyntia; Situmorang, Intan Dewita (Journal of Innovation in Management, Accounting and Business, 2024)
This study is targeted at analyzing regional government fiscal performance from several points of view, including: degree of fiscal decentralization, scale of regional fiscal autonomy, PAD efficiency, PAD effectiveness, regional financial efficiency, regional fiscal effectiveness at BUMD level - contribution. This study is a quantitative descriptive type which is targeted at observing regional financial information in Batubara Regency from 2013 to 2022. In order to collect data, documentation techniques are used. And the analysis uses financial measures.Based on survey results, the scale of fiscal autonomy is classified as very low, namely around 9.78%, the degree of regional fiscal independence is very high at 87.30%, and the degree of fiscal decentralization is classified as very low, namely 8.01%. The effectiveness of PAD is 104.24 % is classified as very effective, PAD efficiency is classified as very efficient at 1.79%, Fiscal effectiveness is 107.83%, making it a very effective measure, Regional budget efficiency is 3.59% which can be said to be very efficient, The level of BUMD contribution is relatively low, namely 1.43 %. This study aims to enable the regional government and community to develop various aspects of Batubara regional government over the last ten years.